The Influence of Smartphone Use on Students' Learning Outcomes in the Subject of Fiqh at Madrasah Aliyah Da’arul Qur’an Karawang - Alfa Briyan Nudin; Debibik Nabilatul Fauziah; Neng Ulya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The reason the researcher chose the title above is because the researcher found a case of students at Madrasah Aliyah Da'arul Qur'an Karawang experiencing a lack of focus on learning and realizing that their report card grades were decreasing in the subject of fiqh due to excessive use of smartphones, which increased in the odd semester then decreased in the even semester due to excessive use of smartphones The use of smartphones for students can facilitate communication, increase knowledge about technological developments, make it easier to find information and make it easier to find information. The approach to this research is a quantitative approach and the type of research is correlational. The sample in this study amounted to 57 people. Data collection techniques used questionnaires and documentation. Data analysis used descriptive and inferential statistics. Based on the results of descriptive statistical analysis, the use of smartphones by students in grades X XI XII at Madrasah Aliyah Daarul Qur'an Karawang is in the moderate category of 88% Based on the results of descriptive analysis of student learning outcomes at Madrasah Aliyah Daarul Qur'an is in the moderate category of 88% Based on the results of simple regression analysis using the SPSS version 25 application, the regression equation test is Ŷ = 56, 238 + 0.228 X. The results of the regression significance test obtained a value of 0.01, then the sig. value. 0.01 <0.05 which means Ha is accepted and H0 is rejected, so it can be concluded that there is an effect of smartphone use on student learning outcomes. And the coefficient of determination value And the coefficient of determination value (R Squiare) is 9.09% which means that the percentage contribution of smartphone use to student learning outcomes is 9.09%.